2021
DOI: 10.3390/en14185877
|View full text |Cite
|
Sign up to set email alerts
|

Third-Order Sliding Mode Applied to the Direct Field-Oriented Control of the Asynchronous Generator for Variable-Speed Contra-Rotating Wind Turbine Generation Systems

Abstract: Traditional direct field-oriented control (DFOC) techniques with integral-proportional (PI) controllers have undesirable effects on the power quality and performance of variable speed contra-rotating wind power (CRWP) plants based on asynchronous generators (ASGs). In this work, a commanding technique based on the DFOC technique for ASG is presented on variable speed conditions to minimize the output power ripples and the total harmonic distortion (THD) of the grid current. A new DFOC strategy was designed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Studies on it have shown how effective this new technology is compared to classic turbines. This new technology is detailed in literature [33,34]. This new technology offers more pneumatic torque than a singlerotor turbine.…”
Section: Dual-rotor Wind Turbinementioning
confidence: 99%
“…Studies on it have shown how effective this new technology is compared to classic turbines. This new technology is detailed in literature [33,34]. This new technology offers more pneumatic torque than a singlerotor turbine.…”
Section: Dual-rotor Wind Turbinementioning
confidence: 99%
“…Direct-drive wind power units actually convert wind energy into mechanical energy in the process of wind power generation into electrical energy [5,6]. For the wind turbine dynamics of the direct-drive wind turbine, the wind power force obtained by the windmill is shown as follows:…”
Section: Analysis Of Wind Turbine Overspeed Mechanismmentioning
confidence: 99%
“…2 Third-order SMC strategy TOSMC technique is among the nonlinear techniques that have been proposed for controlling electrical systems. This technique is a kind of nonlinear technique, which is proposed in [13] to improve the performance and effectiveness of the DTC strategy of the asynchronous generator. This technique reduces ripples in both torque and active power compared to classic techniques such as the PI controller [14].…”
Section: Introductionmentioning
confidence: 99%